FOUNDATIONS OF THE HIGH RISE BUILDING IN THE AREA OF UNDERGROUND MINING - Zotsenko, М. L.; Vynnykov, Yu. L.; Kharchenko, М. O.; Nalyvaiko, L. G.; Mitinskiy, V. M.; Aniskin, A. (Academic journal Industrial Machine Building Civil Engineering, 2017)
Problematic issues of construction of pile-foundation slab of high-rise residential building in the area of underground mining (underground mining with general under working area 25%; the fissured limestone may collapse under the weight of the building) are systematized. The experience of modeling by method of ultimate elements of pile-foundation slab of three-section residential building in the area of underground mining and results of the geodesic monitoring of complex building are presented.
Keywords: underground mining; pile-foundation slab; fissured limestone; method of ultimate elements; stressed-deformed state; geomonitoring